7(x+3)-7=63

Simple and best practice solution for 7(x+3)-7=63 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x+3)-7=63 equation:



7(x+3)-7=63
We move all terms to the left:
7(x+3)-7-(63)=0
We add all the numbers together, and all the variables
7(x+3)-70=0
We multiply parentheses
7x+21-70=0
We add all the numbers together, and all the variables
7x-49=0
We move all terms containing x to the left, all other terms to the right
7x=49
x=49/7
x=7

See similar equations:

| 5x–(x+4)=10–2(x–5) | | 6x+27=-34+31 | | 2x-4+4x-1=8x-3 | | 6−3x=−9+2x | | 5(x+3)=3.5 | | x/5+14=71 | | 3=-5x+9x+6 | | 4x-9x+3=-33 | | 7+3x-12x=3x=3x+1 | | 6x-6=-7+7x | | 6x/32=20 | | 8x-34=2 | | 8x+1x-18=11x+12 | | 3x=15=8x | | 3x+17=9x-6 | | 4+2/3x=4+6/7x | | -6=i/18 | | (x+29)=(3x+5) | | 2a+3=-1/2(6+4a) | | f-8=-42 | | 6x+3=10x-13 | | -18=7+9-10x | | 4k=21 | | 15=4s-3 | | 2(x-4)+3x=5x-8 | | 4x+(-10)=22 | | 0.2k+0.75=0.5k | | -1/2v-5/2=v-7/5 | | -20=-1x-2 | | f-8=42 | | 12x-2-6x=36 | | x/5+7=-6 |

Equations solver categories